Development of sustainable biodegradable lignocellulosic hemp fiber/polycaprolactone biocomposites for light weight applications. (October 2018) - Dhakal, Hom Nath; Ismail, Sikiru Oluwarotimi; Zhang, Zhongyi; Barber, Asa; Welsh, Euan; Maigret, Jean-Eudes; Beaugrand, Johnny
Abstract: Biocomposites with poly( ε -caprolactone) (PCL) as matrix and lignocellulosic hemp fiber with varying average aspect ratios (19, 26, 30 and 38) as reinforcement were prepared using twin extrusion process. The influence of fiber aspect ratio on the water absorption behavior and mechanical properties are investigated. The percentage of moisture uptake increased with the aspect ratio, following Fickian behavior. The hemp fiber/PCL biocomposites showed enhanced properties (tensile, flexural and low-velocity impact). The biocomposite with 26 aspect ratio showed the optimal properties, with flexural strength and modulus of 169% and 285% respectively, higher than those of neat PCL. However, a clear reduction on the mechanical properties was observed for water-immersed samples, with reduction in tensile and flexural moduli for the aspect ratio of 26 by 90% and 62%, respectively than those of dry samples. Summarily, the optimal sample provides an eco-friendly alternative to conventional, petroleum-based and non-renewable composites for various applications.